A total systems design study on the UP sablay system - Lumague, Jeronimo F.; Samoza, Patrick Ryan T.; Sugay, Jamie Francesca F.; Tan, Charles Rainier D.
The Sablay is the official academic costume of the University of the Philippines, which has been used since 1990. An initiative has been launched to redesign and ensure the quality and consistency of the sablay for use in all UP's constituent universities. This total systems design study on the University of the Philippines Sablay System was conducted in order to document and improve the overall system of procurement, licensing, production, quality and distribution for the sablay in consideration of the incoming changes and redesign to the product. There are around 10,000 students who graduate from the University of the Philippines every year. Students and faculty are required to wear a sablay during the graduation exercises. The results of the survey conducted, with 130 respondents, revealed that over 85% of UP students purchased or would purchase a sablay, and that they considered the sablay to be very important to the University of the Philippines' image and branding. The current production of the sablay is handled by two licensed entities outside of the University. There are multiple versions of the sablay available. Arevalo produces handwoven sablays while Maroons retails embroidered sablays from their supplier in Baguio. The two licensees are required by contract to communicate with the UP TTBDO for sales report, Periodic inspections, and license renewals. The production of sablay involves warping, weaving, and finishing. The designs are either woven in or embroidered on top of a woven base. The finished sablays are the distributed to each constituent university. Given the relevance of the sablay to the university's brand, the functions and responsibilities of each involved was reviewed and analysed. Some issues affecting the quality of the UP sablay have been obsereved. The most pressing is the lack of quality standards enforced in the contract of the licensees. In addition, determining material order and production quantities are difficult for the licensees. Finally, the execution of the design is time consuming and difficult. These issues result in multiple variations of the sablay being manufactured and distributed, which compromises the integrity of the UP brand. Several alternatives for the system were developed in order to address these issues and their effect on the quality of the sablay. The most important is the formulation of product standards, including size, thread density, and color. Possible improvements to the weaving technique of the sablay were also developed. The university should also determine the number and sablay sizes of students and provide these to the licensees. The contract terms, including sales reports and periodic inspections. must the strictly implemented. Changes to the ordering system, with the possibility of renting, was also discussed and suggested. The implementation of these alternatives during the pre-production and post-production phases of the UP sablays system would result in the reduced variability and better execution of the sablay design. The enhanced and consistent quality of the sablay would then ensure the integrity of the UP brand.